Separating the substance from the noise: a survey of the Black arts movement - Hutchinson, Yvette (2003)
This thesis will survey the Black Arts Movement in America from the early 1960s to the 1970s. The Movement was characterised by a proliferation of poetry, exhibitions and plays. Rather than close textual analyses, the thesis will take a panoramic view of the Movement considering the movement's two main aims: the development of a canon of work and the establishment of black institutions.